Lithuanian Consumers’ Preferences and their Willingness to Pay for “Green” Energy - Štreimikienė, Dalia; Pušinaitė, Rasa (Ekonomika, 2006)
The main advantage of renewables over conventional energy sources is that they contribute to the preservation of public goods. namely clean air and climate stability. Because of the non-excludable and non-rival characteristics of these goods. private actors are not prepared to invest in something which everyone can acquire free of charge. in such conditions the diffusion of renewables cannot be assured spontaneously by the markets unless it is effective. This has been the position of economists for a long time but there is now some evidence that certain groups may in fact buy some goods that are more expensive because they have some public good benefits.The arrangement under a liberalized electricity market which enables consumers who want to pay for green electricity and to purchase green electricity from a supplier on a higher price is one response to the is demand. The is method was testes as successful in many countries (Germany, the Netherlands, Nordic countries, the USA) and can provide an insight into the preferences of consumers and their willingness to pay for renewables. Experience in some countries showed that the proportion of green electricity purchases is low (around 2-3%) except in cases where there are strong incentives in the form of tax exemptions for electricity consumers, like in the Netherlands. The percentages of those wiling to buy “green” electricity can be increased by information campaigns, education, and training.The aim of the article was to assess Lithuanian citizens’ attitudes toward “green” energy and to estimate their possibilities and willingness to buy “green” electricity. Population perception of the “green energy” benefits and preferences plays an important role nowadays, and ethical environment policy methods are widely spread in the world. Lithuanian citizen have no possibility to buy “green” energy, because the energy market isn’t fully open in Lithuania. The energy market will be open in 2007 and all electricity users will have the opportunity to choose energy supplier. It is important to prepare for market opening and the develop consumer’s preferences and their acceptances of “green” energy and willingness 10 pay more for such energy.